2020
DOI: 10.1155/2020/8847306
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A Is a Biomarker of Disease Activity and Health-Related Quality-of-Life in Patients with Antineutrophil Cytoplasmic Antibody-Associated Vasculitis

Abstract: Serum amyloid A (SAA) is one of the acute phase proteins synthesized in hepatocytes and secreted by various inflammation or infectious stimuli. We investigated the clinical implication of measuring SAA in patients with antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitis (AAV). Seventy-five patients who had been classified as AAV and enrolled in our prospective observational cohort for AAV patients were included. Clinical and laboratory data were obtained on the day of blood sampling, and SAA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Some biomarkers such as PCT, CRP, SAA, and ESR are helpful in the identification of infection [ 8 , 9 , 23 27 ], yet remain unclear for AAV patients. According to previous studies, it seems that higher CRP is more likely to indicate lung infection [ 24 ], while ESR is more likely to indicate AAV activity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some biomarkers such as PCT, CRP, SAA, and ESR are helpful in the identification of infection [ 8 , 9 , 23 27 ], yet remain unclear for AAV patients. According to previous studies, it seems that higher CRP is more likely to indicate lung infection [ 24 ], while ESR is more likely to indicate AAV activity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the improper treatment of pulmonary complications in AAV patients, it is urgent to identify reliable markers to distinguish the pulmonary lesions of infection and vasculitis. Recently, a panel of biomarkers, including neutrophil-to-lymphocyte ratio (NLCR), serum amyloid A (SAA), as well as pro-calcitonin (PCT) have been used to identify and assess the infectious status in clinics [ 8 , 9 ]. However, to our knowledge, similar markers for assessing the infection of AAV patients have not yet been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, PR3 and MPO titers were not signi cantly different between the LI and NI groups, suggesting that patients with high PR3 and MPO may be more likely to have pulmonary lesions, but these two indexes cannot predict whether they were complicated by a lung infection. Some biomarkers such as PCT, CRP, SAA, and ESR are helpful in the identi cation of infection [8,9,[20][21][22][23] , yet remain unclear for AAV patients. According to previous studies, it seems that higher CRP is more likely to indicate lung infection [24] , while ESR is more likely to indicate AAV activity [25] .…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the improper treatment of pulmonary complications in AAV patients, it is urgent to identify reliable markers to distinguish the pulmonary lesions of infection and vasculitis. Recently, a panel of biomarkers, including neutrophil-to-lymphocyte ratio (NLCR), serum amyloid A (SAA), as well as pro-calcitonin (PCT) have been used to identify and assess the infectious status in clinics [8,9] . However, to our knowledge, similar markers for assessing the infection of AAV patients have not yet been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…The role of SAA in autoimmunity is underscored by data showing that SAA are associated with clinical severity and disease susceptibility. Several authors, comparing serum SAA levels between healthy and diseased individuals, showed an increase in SAA concentration during autoimmune diseases (Ahmed et al., 2022; Shen et al., 2015; Wang et al., 2020; Yoon et al., 2020). Notably, SAA can act directly on T cells and promote Th17 cell programming and response amplification, which revealed in inflammatory bowel disease (IBD) and experimental autoimmune encephalomyelitis (EAE) models (Lee et al., 2020).…”
Section: Introductionmentioning
confidence: 99%